$θ(τ_1,τ_2)$-continuity for Functions (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces a new class of functions between bitopological spaces, namely $θ(τ_1,τ_2)$-continuous functions. Moreover, several characterizations and some properties concerning $θ(τ_1,τ_2)$-continuous functions are investigated.
Keywords: $(τ_1,τ_2)θ$-open set; $θ(τ_1,τ_2)$-continuous function